A review of energy-aware multi-objective hybrid flow shop scheduling with parallel machines in manufacturing systems - Saptiyadi, Arif; Arina, Faula; Kurniawan, Bobby (Universitas Sultan Ageng Tirtayasa, 2024)
Hybrid flow shop scheduling (HFSS) with parallel machines has gained attention among researchers in manufacturing systems because of its critical role in enhancing production efficiency. This type of production system is widely implemented in modern factories today. This production system combines the characteristics of a job shop and flow shop, with each stage having more than one machine capable of processing all jobs. This review provides a comprehensive analysis of HFSS, focusing on the integration of parallel machines to address real-world manufacturing complexities. Key topics covered include problem formulations, mathematical models, heuristic and metaheuristic approaches, and recent advancements in solution techniques. The study highlights the advantages and limitations of various methodologies, emphasizing their applicability in diverse industrial contexts. Furthermore, the review identifies current trends, such as the incorporation of artificial intelligence and Industry 4.0 technologies, as well as gaps in the literature that require further exploration. By synthesizing existing research, this paper aims to guide future studies and offer practical insights for practitioners aiming to enhance scheduling performance in dynamic manufacturing environments.